The influence of carbon nanotubes characteristics in their performance as positive electrodes in vanadium redox flow batteries. (March 2015) - González, Zoraida; Álvarez, Patricia; Blanco, Clara; Vega-Díaz, Sofía; Tristán-López, Ferdinando; Rajukumar, Lakshmy Pulickal; Cruz-Silva, Rodolfo; Elías, Ana Laura; Terrones, Mauricio; Menéndez, Rosa
Highlights: Different MWCNTs as positive electrodes in vanadium redox flow batteries. Influence of their different characteristics on the response towards VO 2+ /VO2 + Enhanced performance of MWCNT-Cs, sample of nanotubes with the highest Csp 2 content. Encouraging energy efficiency values in a VRB with MWCNT-Cs as positive electrode. Abstract: Three types of multi-walled carbon nanotubes are investigated as electrodes in the positive half-cell of a vanadium redox flow battery (VRFB). Pure (MWCNTs), nitrogen-doped (CN x MWNTs) and oxygen functionalized (MWCNT-Cs) carbon nanotubes exhibit significant structural differences at the nanoscale, as well as different chemical and physical properties. The influence of such different characteristics on the electrochemical behavior towards the VO 2+/ VO2 + redox reactions is investigated by cyclic voltammetry, electrochemical impedance spectroscopy and charge/discharge experiments. MWCNT-Cs exhibit the best performance despite not having the largest specific surface area, neither the greatest amount of oxygen nor nitrogen functional groups on their surface. Therefore, their enhanced performance in terms of electrochemical activity and kinetic reversibility towards the vanadium reactions and energy efficiency of the corresponding static battery, are attributed to the highest sp 2 carbon content, which brings the highest electrical conductivity. These results represent a significant advance in the fundamental understanding and design of effective electrode materials that will lead to more efficient batteries.